Enhancement of channel coding technique for mobile system in 5G network / N. M. Salih ... [et al.] - Salih, N. M.; Saleh, M. Z; Radzi, H. M.; Johor, H.; Sulong, S. M.; M. Said, M. S. (2020)
5G technology is the future of wireless communication due to the growth of wireless technology today. This is because the current 4G technology is lack of capabilities such as unstable latency, average speed data transmission and low voice quality. The capabilities of 5G technology which offer higher-speed user capacity, good voice quality, super-fast data transmission, ultra-low latency and tolerance to the noise make this technology more compatible to support millions of devices at ultrafast speed. The usher in the fourth industrial revolution also can be realized with this 5G technology that will affect to increase a country economy. This technology also benefits the community by having much useful technology such as autonomous vehicle and object tracking. The system model comprising digital modulator with block coding technique to maintain its reliability and operability. Thus, the objective of this project is to invent an enhancement coding technique, that is Asymmetric Arithmetic Coding (AAC) added to the existing model to further improve the signal reliability and reduce probability of error for the application of mobile communications to visualize the proof concept of using enhancement coder will support the stability of 5G network. Furthermore, the system is applying mathematical formulation for the error correction coding technique at the receiver, to enhance the computational complexity and finally measure the performance of the complete system. It is said that the enhancement of the channel coding technique, can support the uninterruptible services for mobile communications in 5G network. Overall, the communication system model will lead to the mutual harmonization among society with new parameters of mobile system.